The archipelago Italy since 1945 - Foot, John 1964- (Bloomsbury Publishing, 2018)
Cover -- Half Title -- Dedication -- By the same author -- Title Page -- Contents -- Map -- Preface -- Introduction: 1945 - Year Zero -- The Return -- Cycling Back to Normality -- 1946: Viva Toscanini! -- Paisà -- Republic of the Dead -- The Duce's Body -- 1 Rebuilding and Remaking Italy -- Democracy -- Republic or Monarchy? -- The Referendum Campaign -- To the Polls -- Counting the Votes -- Another King Departs -- Resistance, Anti-Fascism and Post-War Italy -- Qualunquismo and Anti-Politics -- Figureheads and Symbols in Republican Italy -- Building a New State: Italy's Constitution -- Cold War -- April and July 1948: Election and Revolution - Counting Votes, Weighing Votes -- July 1948: Italy at the Barricades58 -- Revolution? -- Parishes, Priests and Catholic Culture -- The White Whale: Christian Democrats -- Corridors of Power -- Reds: Communists and the Communist Party in Italy after 1948 -- Cult of Personality -- The 'Big Moustache' is Coming: Stalin, the Soviet Union and Italian Communism -- Following Orders? -- A Mass Party -- Legacies of War: Trieste -- 1956: The Secret Speech and Hungary -- Heart of Europe: Altiero Spinelli, Italy and European Integration -- 2 Takeoff: Italy in the Boom Years -- Final Act? Post-War Peasant Struggles and Reform -- Exodus: Stories from the Great Migration -- The End of Rural Italy -- The End of Sharecropping -- Former Jobs and Nostalgia -- Money, Money, Money -- Factories and Workers -- A Love Affair: Italians and Cars -- Motorway of the Sun -- Fiataly -- Riding the Tiger? Planning and Cities -- 1963: Vajont -- Landslip: Agrigento - July 1966 -- 1966: Mud Angels -- The Brick Kings -- Cultural Change and the Boom: Italy's Soundtrack -- Cultural Change and the Boom: The Magic Rectangle - Italy and Television -- Love and Marriage before and during the Boom: Public Sinners? -- Marriage, Divorce and the Law.